2017
DOI: 10.4236/ijcce.2017.61002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Asphaltene Deposition and Precipitation in Production Tubing

Abstract: Asphaltenes are complex molecular entities, which together with resins, aromatic hydrocarbons and saturates forms the crude oil. Asphaltenes and resins are in the thermodynamic equilibrium at static reservoir condition. However, asphaltene can precipitate due to changes in thermodynamic condition. Asphaltene deposition in production tubings has been an outstanding problem with wide economic impact on the oil industry. Meanwhile, the use of real-time tools to monitor depositions along the well is of great diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…For this reason, the predictive capabilities of PC-SAFT EOS models are somewhat limited and are not studied in this work. It is important to say that the performance of the solid–liquid equilibrium model to describe asphaltene precipitation, which is also used in asphaltene deposition studies, is widely reported in the literature. …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the predictive capabilities of PC-SAFT EOS models are somewhat limited and are not studied in this work. It is important to say that the performance of the solid–liquid equilibrium model to describe asphaltene precipitation, which is also used in asphaltene deposition studies, is widely reported in the literature. …”
Section: Introductionmentioning
confidence: 99%